Tuberculosis Outbreak in an Educational Institution in Henan Province, China - Li, Hui; Liu, Chunfa; Liang, Minghui; Liu, Dongxin; Zhao, Bing; Shi, Jie; Zhao, Yanlin; Ou, Xichao; Zhang, Guolong (Frontiers in Public Health, 2021)
In 17th June 2018, a case of pulmonary tuberculosis (TB) was reported among students at a senior high school in Luoning, China. The outbreak encompassed a total of 23 cases along with TB screening in whole school by means of PPD and chest X-ray by the end of September 2018, the entire 9 cases cultured positive had epidemiological association. All of the 9 Mycobacterium tuberculosis isolates available were sensitivity to all drugs tested and had similar 15 loci mycobacterial interspersed repetitive-unit–variable-number tandem-repeat (MIRU-VNTR) profile. Whole-genome sequencing (WGS) of the Mycobacterium tuberculosis (Mtb) isolates revealed 20 variable nucleotide positions within 8 cases, indicating a clonal outbreak. The index case which was first identified and diagnosed is separated from the cluster by a minimum number of 95 distinct SNPs. Minimum distance spanning tree (MST) indicted that the 8 cases were indeed part of a single transmission chain. Conclusions this is an epidemic situation of TB outbreak exposed by the aggrieved index case at school which caused by the veiled infectious case keeping back the truth of suffering from TB and attending school simultaneity.